Cumplimiento en la implementación de la facturación electrónica como herramienta de control de la auditoría interna en la empresa Patio Industrial S.A.S en la ciudad de Santa Marta (2023)
This paper is based on the main topic that leads to the issue of electronic invoicing, just like the compliance matrix which objective is to analyze the process that are involved in the creation of an electronic invoicing; however, taking Decree 2242 of 2015 as a reference, which clarifies the guidelines in the development of this one. It develops an internal audit plan to determinate if the company is following the regulation and what changes or impact generates inside the electronic invoicing. For this purpose, was made a descriptive methodology with a qualitative analytical approach, that will be taken as a population for the company Patio Industrial S.A.S in the city of Santa Marta. As a result, it was possible to obtain within the scope of the objectives that the company is constituted through the corporate name and the impact generated by the compliance matrix showed that the company is following the current regulatory processes for the current fiscal year. The development of a system that allows you to optimize your process, resulting in efficiency and effectiveness. Conclusions are provided to encourage the realization of the same compliance matrix so it can be used within its internal audit